Failure probability and location identification of damaged insulators using normal function and monitored leakage current. - Moein Monemi; Seyed Mohammad Shahrtash; Mohsen Kalantar (PLoS ONE)
The main task of insulators is to isolate the conductor from the tower. These insulators must be able to isolate the high voltages of the transmission lines from the tower without having a leakage current (LC). These insulators get damaged over time and may not work properly. Currently, identifying and replacing defective insulators, in addition to being time-consuming, requires frequent and long blackouts to be imposed on the customers. For this reason, this paper examines the problems and failures caused by the use of insulators in networks with different voltage levels and suggests the failure rate for planning the maintenance of these electrical network equipment. Based on this, according to the insulator leakage current data, the failure or damage rate of the insulator equipment will be investigated using the normal distribution. This distribution function will calculate the probability of insulator failure using LC data, and then the failure rate and the priority of insulator maintenance will be measured compared to other data. According to this article, the final goal of the proposed methodology will be to determine the failure rate as well as decision-making for the maintenance of the insulator equipment and finally determine the damaged insulator among all the insulators of the electrical network. By identifying the insulators with a higher failure rate, the maintenance team will decide to repair or replace the damaged insulator before the insulator failure and the fault in the power grid.